DEPOSITIONAL ARCHITECTURE AND DIAGENESIS OF THE CLASTIC SEDIMENTARY SYSTEMS OF THE BELAGA, BALINGIAN AND BEGRIH FORMATIONS, ALONG THE MUKAH - SIBU - SELANGAU TRANSECT, SARAWAK - NUGRAHENI, ROSMALIA DITA (2015)
Research study was carried out along the Mukah-Sibu-Selangau transect, Sarawak. The deep marine turbiditic Belaga Formation (Fm.) is present as the oldest sedimentary formation in the Sibu-Selangau transect, which is underlying the coastal plain deposits of the Balingian and Begrih Formations (Fms.) along the Mukah- Selangau transect. This study utilizes outcrop data which resolve small scale features required for the examination of its sedimentology, to reconstruct facies architecture and depositional history as a reference to build the diagenesis history.